Double-blind comparison between optical and conventional impressions for the production of mandibular advancement devices - Edoardo Bianchi; Andrea Toffoli; Marzia Segù; Alberto Azzi; Guido Maria Macaluso; Simone Lumetti; Edoardo Manfredi (Publymed, 2023)
Background: Obstructive sleep apnea syndrome (OSAS) is a sleep disorder with a high social and health impact. Mandibular advancement devices (MADs) are considered a viable treatment option and a possible first-line treatment in this setting. No study in the literature has investigated clinical aspects of these devices in relation to the procedures used to manufacture them. The aim of this study was to compare the clinical adequacy of MADs produced starting from conventional analog versus digital impressions; Methods: Four patients were recruited. For each of them, two MADs were produced: one starting from an intraoral scan and the other from the digitalization of a plaster model based on analog impressions. Clinical parameters of the two devices were evaluated and compared; Results: No statistically significant differences in the clinical parameters evaluated were found between the two groups of devices; Conclusion: Optical and conventional impressions show similar accuracy in the production of MADs.